2004
DOI: 10.1080/10446670410001670544
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Pollen Counts and Weather Variables in East‐Mediterranean Coast of Turkey

Abstract: Background: Aeroallergen sampling provides information regarding the onset, duration and severity of the pollen season that clinicians use to guide allergen selection for skin testing and treatment. Objectives: This atmospheric survey reports (1) airborne pollen contributions in Adana in one-year period (2) pollen onset, duration and peak level (3) the relationship between airborne pollen and selected meteorological variables and; (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 8 publications
(11 reference statements)
3
25
0
2
Order By: Relevance
“…19,22 Symptom severity (and subsequent rescue medication use) is associated with pollen exposure, 29 and in this study the average and peak pollen counts were relatively low compared with those in the European grass AIT trials, 19,22 which likely influenced the DMS. Given the low grass pollen counts during the GPS, it is not unexpected that rescue medication levels did not reach higher magnitudes.…”
Section: Discussionmentioning
confidence: 94%
“…19,22 Symptom severity (and subsequent rescue medication use) is associated with pollen exposure, 29 and in this study the average and peak pollen counts were relatively low compared with those in the European grass AIT trials, 19,22 which likely influenced the DMS. Given the low grass pollen counts during the GPS, it is not unexpected that rescue medication levels did not reach higher magnitudes.…”
Section: Discussionmentioning
confidence: 94%
“…Day 1 was significantly higher than the rest with a mean of 1.7 9 10 4 pollen grains m -3 , while the other days had a mean value of 3.1 9 10 3 pollen grains m -3 . A Spanish study measuring pollen in an urban setting for 2 years found a maximum daily concentration of 730 pollen grains m -3 (Tormo-Molina et al 2009), and a British and a Turkish study both in cities found a total annual pollen count of respectively 3.0 9 10 4 and 3.3 9 10 4 pollen grains m -3 (Altintas et al 2004;Pashley et al 2009). …”
Section: Discussionmentioning
confidence: 95%
“…A positive SPT result to at least one of the allergen extracts tested was accepted as the presence of sensitization for that patient. We did not use a common aeroallergen extract, ragweed, of the pan-European GA 2 LEN skin test study because of the undetectable pollen counts for ambrosia in the atmosphere of Turkey [10,11]. …”
Section: Methodsmentioning
confidence: 99%